The Influence of Socio-Economic, Religiosity, and Coping Strategies on Husband and Wife Interaction Cianjur Disaster Survivors - Siroj, Eko Yuliarti; Sunarti, Euis; Krisnatuti, Diah; Muflikhati, Istiqlaliyah; Johan, Irni Rahmayani (TDMRC, Universitas Syiah Kuala, 2024)
Family interactions are needed in disasters because they play an important role in strengthening the emotional bonds between family members. In husband-wife interaction, different family roles and functions make couples feel complementary. This study aims to analyze the influence of socioeconomics, religiosity, and coping strategies on the interaction of husband and wife families of earthquake survivors in the Cianjur district. The study population was families of earthquake survivors in Cianjur Regency. The research sample was selected using a stratified non-proportional random sampling technique based on lightly damaged and heavily damaged houses. Respondents in the study were the wives of earthquake survivors in Cianjur Regency, with 200 respondents. Data processing and analysis used Microsoft Excel, Statistical Package for Social Science (SPSS) 25.0 for descriptive analysis, and Structural Equation Modeling-Partial Least Square (SEM-PLS) for influence analysis. The results showed high religiosity, spousal interaction involvement, and high satisfaction. Coping strategies, frequency of husband and wife interaction, and potential conflict between husband and wife are in the medium category. This study shows that husband and wife interaction is positively influenced by husband and wife's education, age of marriage, family income-expenses, and religiosity and negatively influenced by husband and wife's age. In addition, religiosity also has a positive effect on coping strategies. This study implies that families of disaster survivors are expected to increase family religiosity to improve husband and wife interactions. Local governments are advised to conduct adequate education for community readiness to face disasters.